Modified current follower-based immittance function simulators. Issue 12 (2nd December 2017) - Alpaslan, Halil; Yuce, Erkan
ABSTRACT: In this paper, four immittance function simulators consisting of a single modified current follower with single Z− terminal and a minimum number of passive components are proposed. The first proposed circuit can provide + L parallel with + R and the second proposed one can realise − L parallel with − R . The third proposed structure can provide + L series with + R and the fourth proposed one can realise − L series with − R . However, all the proposed immittance function simulators need a single resistive matching constraint. Parasitic impedance effects on all the proposed immittance function simulators are investigated. A second-order current-mode (CM) high-pass filter derived from the first proposed immittance function simulator is given as an application example. Also, a second-order CM low-pass filter derived from the third proposed immittance function simulator is given as an application example. A number of simulation results based on SPICE programme and an experimental test result are given to verify the theory.